Simulation Calculation and Influence Analysis of High Altitude Wind Speed in Different Directions of Tower Solar Energy Receiver - Lu DING; Xinyue XIAO; Zhengwen XI; Wenhan HUA (发电技术)
As the key equipment of the tower thermal power station, the safe and efficient operation of the receiver has an important impact on the reliability and economy of the power station. The receiver is installed on the top of the tower, and the environmental meteorological factors, especially the wind speed, are directly related to the operation control strategy of the receiver and the concentrating system. Based on this, this paper used numerical simulation method to study the wind speed characteristics of the high-altitude tower receiver in different directions. The trend of wind speed on the surface of the tube panel changing with the environmental wind speed and direction was obtained. In addition, the wind speed calculation correlation was fitted and the calculation wind direction was agreed in detail. This work has important guiding significance for the accurate calculation of heat loss, the accurate evaluation of efficiency and the safe and reliable operation of the receiver.